Spiny lobsters prefer native prey over range-extending invasive urchins. (8th April 2022) - Smith, Jennifer E; Keane, John; Mundy, Craig; Gardner, Caleb; Oellermann, Michael
Abstract: Climate change increases the need to control range-extending species, which adversely impact their recipient ecosystem. Increasing populations of resident predators may be effective to counter such range-extension, but only if they consume the novel invaders at sufficient rates. In South-East Australia, poleward range-extending Longspined Sea Urchins ( Centrostephanus rodgersii ) are causing catastrophic ecological habitat transition to extensive urchin barrens. Tasmanian native Southern Rock Lobster ( Jasus edwardsii ) is a potential predator that could control further urchin expansion. Experimental feeding trials showed that range-extending Longspined Sea Urchins are the least preferred prey choice for Southern Rock Lobsters (3.8% predation events), when compared to three local species: abalone, urchins, and snails (36.6, 32.6, and 27%). Interestingly, habitat origin and naivete of lobsters to urchins affected urchin consumption with 85% being consumed by lobsters originating from urchin barrens. Low predation rates on Longspined Sea Urchin suggest that resident lobsters are unlikely to control further barren expansion unless a behavioural shift occurs. Results imply that potential control of Longspined Sea Urchins by Southern Rock Lobsters has previously been overestimated. Additional control methods are needed to safeguard ecological communities and important commercial stocks from this climate change-induced, range-extending pest species.